2011
DOI: 10.1097/shk.0b013e3182094a0b
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Shock Paradox and Cardiac Myocytes

Abstract: The induction of the heat shock response is accepted to be a protective response, reducing injury and improving cell survival. However, when inflammation precedes heat shock there is an unexpected increase in injury, known as the heat shock paradox, which is hypothesized to be a mechanism underlying multi-organ dysfunction. We hypothesized that the heat shock paradox would occur in adult cardiac myocytes and that heat shock factor (HSF)1 would contribute to injury. Heat shock (HS) at 42°C and TNF (10 ng/ml) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
1
4
0
1
Order By: Relevance
“…However, if Hsp25 expression is induced after injury (via HSF-1 activation in response to Dox-induced oxidative stress), it is cytotoxic and aggravates apoptosis in the heart (Vedam et al, 2010). In support of these findings, recent studies by the Knowlton group have demonstrated that TNF-␣ injury was worsened by HSF-1 activation induced by heat stress after injury (Kobba et al, 2011). Taken together, the accumulated data indicate that overexpression of eHsp25 by any combined therapy during the treatment of cancer using Dox might result in the suppression of cardiomyopathy.…”
Section: Discussionsupporting
confidence: 72%
“…However, if Hsp25 expression is induced after injury (via HSF-1 activation in response to Dox-induced oxidative stress), it is cytotoxic and aggravates apoptosis in the heart (Vedam et al, 2010). In support of these findings, recent studies by the Knowlton group have demonstrated that TNF-␣ injury was worsened by HSF-1 activation induced by heat stress after injury (Kobba et al, 2011). Taken together, the accumulated data indicate that overexpression of eHsp25 by any combined therapy during the treatment of cancer using Dox might result in the suppression of cardiomyopathy.…”
Section: Discussionsupporting
confidence: 72%
“…This finding is consistent with a recent report that HSP32/HO-1 was still induced by heat shock in the presence of an Hsf-1 inhibitor in cardiac myocytes. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Hasonló eredmények-ről olvashatunk szíven [32], agyon [33] és vesén [34] végzett kísérletek esetében is. A HSP-72 szerepe való-színűleg igen szerteágazó, feltételezhetjük, hogy az ischaemia-reperfúzió, illetve a különböző kezelések hatására létrejövő celluláris védelmi mechanizmusok részt-vevője [35,36].…”
Section: Irodalomunclassified